2022
DOI: 10.3390/jcm11040992
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Predictive Value of the C2HEST Score in Elderly Subjects with COVID-19—A Subanalysis of the COLOS Study

Abstract: Senility has been identified among the strongest risk predictors for unfavorable COVID-19-outcome. However, even in the elderly population, the clinical course of infection in individual patients remains unpredictable. Hence, there is an urgent need for developing a simple tool predicting adverse COVID-19-outcomes. We assumed that the C2HEST-score could predict unfavorable clinical outcomes in the elderly subjects with COVID-19-subjects. Methods: We retrospectively analyzed 1047 medical records of patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These predicted values by the C2HEST score were comparable to values predicted by the VACO index and presented in this article. Our previously published papers [17,18] state that the elderly population is more likely to be hospitalized or admitted to an intensive care unit and that advanced age has a positive correlation with increasing hospitalization time. In our study, patients from the extreme risk stratum had the longest hospitalization time when compared to patients from other risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…These predicted values by the C2HEST score were comparable to values predicted by the VACO index and presented in this article. Our previously published papers [17,18] state that the elderly population is more likely to be hospitalized or admitted to an intensive care unit and that advanced age has a positive correlation with increasing hospitalization time. In our study, patients from the extreme risk stratum had the longest hospitalization time when compared to patients from other risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a simple, fast, well-validated scoring system dedicated to the HF subpopulation is still missing. Taking into account some encouraging data from our previous analyses concerning other subpopulations of COVID-19 patients [ 8 , 9 , 19 ], we decided to validate the C 2 HEST score system in terms of heart failure subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, Liang et al [ 7 ] demonstrated that C 2 HEST score could also predict adverse clinical outcomes, including death and hospitalization, among patients with heart failure. Considering that individual components of the C 2 HEST (C2: CAD/COPD; H: Hypertension; E: Elderly (Age ≥ 75); S: Systolic HF; T: Thyroid disease) are parallel to COVID-19 mortality risk factors, juxtaposing it with the outcomes of recently published studies [ 8 , 9 , 10 ] suggesting that this simple scoring system has the ability to predict outcomes in several COVID-19 subpopulations, we designed this study to evaluate the predictive value of C 2 HEST score in patients with heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%
“…Along with hypoxemic respiratory failure, acute decompensation of pre-existent comorbidities within the first week of infection was the most common cause of death [22]. Several studies investigated prognostic factors in elderlies with COVID-19 infections [23][24][25][26][27]. Scheffler et al investigated the prognostic role of subcutaneous and visceral adipose tissue using a quantification fat area on 64 patients with a mean age of 86.4 ± 6.0 years [23].…”
mentioning
confidence: 99%
“…The C 2 HEST is a stratification scoring system to assesses the risk of developing atrial fibrillation. Rola et al [25] demonstrated that the C 2 HEST was effective in predicting six-month and in-hospital mortality in 1047 elderlies with COVID-19. Moreover, the C 2 HEST was also valid in predicting the risk of non-fatal events, including cardiogenic shock and acute kidney and heart failure in elderlies affected by COVID-19 [25].…”
mentioning
confidence: 99%